Republic of Armenia : Poverty Reduction Strategy Paper Progress Report; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2006)
This Joint Staff Advisory Note (JSAN) discusses Poverty Reduction Strategy Paper (PRSP) for Armenia, which focuses on the government's commitment to equitable growth and sustained poverty reduction. It reports on the progress in addressing issues raised in the previous JSAN, and provides IMF staff's advice on key priorities for strengthening the PRSP process further. The second PRSP Progress Report provides strong evidence of rapid economic growth, a notable reduction in poverty, and a number of other accomplishments, particularly in fiscal policy and social service delivery.